PENGARUH EARNING PER SHARE TERHADAP DIVIDEN PER SHARE SAHAM PADA PERUSAHAAN JASA SUBSEKTOR KONSTRUKSI BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Subianto, Subianto; Rohim, Nursainatu (Balance : Jurnal Akuntansi dan Bisnis, 2022)
The study discusses the influence of Earning Per Share toward Dividend Per Share at The Building Construction Subsector Services Registered in Indonesia Stock Exchange. The Data was conducted through pursposive sampling technique. This is quantitative study which has two variable. The data was analysed through desciptive method and tested by simple liniear regression test, where Y = 18.796 + 0.092X. The result showed  of the normality test shows that the significance value of the data that has been processed is 0.675, where the significance value is greater than 0.05. So it can be concluded that the data is statistically normally distributed and suitable for use as data for research. The results of significant influence of influence of Earning Per Share toward Dividend Per Share at The Building Construction Subsector Services Registered in Indonesia stock Exchange by p-value 0,001<0,025 and t value 3,406 > t-Table 2,016. It mean that the null hypothesis was rejected. From the summary table of the simple linear regression test above, it can explain the magnitude of the correlation or relationship value, namely R of 0.461. This means that the profit per share affects the dividend per share is 46.1%, while the remaining 53.9% (100% - 46.1%) is influenced by other factors outside the variable x